PERAN SEKOLAH PENGGERAK DALAM MENINGKATKANKOMPETENSI PESERTA DIDIK DI SMP NEGERI 7 MAKASSAR - Bakhtiar Bakhtiar; Muh Sudirman; Juniawaty Norma Saputri (Jurnal Tomalebbi, 2023)
Abstract: This research aims to determine (1) The implementation of driving school activities at SMP Negeri 7 Makassar (2) The impact of driving school activities at SMP Negeri 7 Makassar (3) What factors influence the implementation of the driving school program at SMP Negeri 7 Makassar. This research method uses a descriptive qualitative research type with a qualitative approach. The data sources used consist of primary data and secondary data with data collection techniques and procedures, namely observation, interviews and documentation. The data analysis used is a. Data reduction; b. Presentation of data ordisplay;c. Drawing data conclusions and verifying is the final activity of qualitative research.The results of this research conclude that (1) Implementation of driving school activities at SMP Negeri 7 Makassar includes: (a) Human resource development through PMO, IHT, Workshops, Independent Training, and Utilization of PMM. (b) Implementing a learning process with a new paradigm through implementing teaching modules, teachers acting as facilitators, and integrating technology. (c) Optimizing school digitalization through the procurement of computers, smart TVs and developing school websites. (2) The impact of driving school activities at SMP Negeri 7 Makassar provides an increase in students in cognitive and affective terms. Then, the impact on teachers provides freedom to innovate in designing learning plans. And the impact on schools is optimizing facilities, infrastructure and systems based on digital management. (3) Factors that influence the implementation of the driving school program through (a) adequate facilities and infrastructure, (b) optimal teacher competency. (c) Funding for activities provided by the central and regional governments.Keywords: Driving School, Competence, and Students. Abstrak: Penelitian ini bertujuan untuk mengetahui (1) Pelaksanaan kegiatan sekolah penggerak di SMP Negeri 7 Makassar (2) Dampak kegiatan sekolah penggerakdi SMP Negeri 7 Makassar (3) Faktor-faktor apa yang memengaruhi pelaksanaan program sekolah penggerak di SMP Negeri 7Makassar. Metode penelitian ini menggunakan jenis penelitian kualitatif deskriptif dengan pendekatan kualitatif. Adapun sumber data yang digunakan terdiri dari data primer dan data sekunder dengan teknik dan prosedur pengumpulan data yaitu observasi, wawancara dan dokumentasi. Analisis data yang digunakan yaitu a. Reduksi data; b. Penyajian data atau display;c. Penarikan kesimpulan data dan verifikasi artinya kegiatan akhir penelitian kualitatif.Hasil penelitian ini menyimpulkan bahwa (1) Pelaksanaan kegiatan sekolah penggerak di SMP Negeri 7 Makassar meliputi: (a) Pengembangan sumber daya manusia melalui PMO, IHT, Workshop, Pelatihan Mandiri, dan Pemanfaatan PMM. (b) penerapan proses pembelajaran dengan paradigma baru melalui pengimplementasian modul ajar, guru berperan sebagai fasilitator, dan pengintegrasian teknologi. (c) pengoptimalan digitalisasi sekolah melalui pengadaan komputer, smart tv dan pengembangan website sekolah. (2) Dampak kegiatan sekolah penggerakdi SMP Negeri 7 Makassar memberikan peningkatan terhadap peserta didik dalam hal kognitif dan afektifnya. Kemudian, dampak kepada guru memberikan kebebasan berinovasi dalam merancang perencanaan pembelajaran. Dan dampak kepada sekolah yaitu pengoptimalan sarana, prasarana dan sistem berbasis manajemen digital. (3) Faktor-faktoryang memengaruhi pelaksanaan program sekolah penggerak melalui (a) Sarana dan pra-sarana yang memadai, (b) kompetensi guru yang optimal. (c) pendanaan kegiatan yang diberikan oleh pemerintah pusat maupun daerah.Kata Kunci: Sekolah Penggerak, Kompetensi, dan Peserta didik